Novel microbial epoxide hydrolases for biohydrolysis of glycidyl derivatives - Kotík, Michael; Břicháč, Jiří; Kyslík, Pavel (Journal of biotechnology, 2005)
Microbial isolates from biofilters and petroleum-polluted bioremediation sites were screened for the presence of enantioselective epoxide hydrolases active towards tert-butyl glycidyl ether, benzyl glycidyl ether, and allyl glycidyl ether. Out of 270 isolated strains, which comprised bacteria, yeasts, and filamentous fungi, four were selected based on the enantioselectivities of their epoxide hydrolases determined in biotransformation reactions. The enzyme of Aspergillus niger M200 preferentially hydrolyses (S)-tert-butyl glycidyl ether to (S)-3-tert-butoxy-1,2-propanediol with a relatively high enantioselectivity (the enantiomeric ratio E is about 30 at a reaction temperature of 28 degrees C). Epoxide hydrolases of Rhodotorula mucilaginosa M002 and Rhodococcus fascians M022 hydrolyse benzyl glycidyl ether with relatively low enantioselectivities, the former reacting predominantly with the (S)-enantiomer, the latter preferring the (R)-enantiomer. Enzymatic hydrolysis of allyl glycidyl ether by Cryptococcus laurentii M001 proceeds with low enantioselectivity (E=3). (R)-tert-Butyl glycidyl ether with an enantiomeric excess (ee) of over 99%, and (S)-3-tert-butoxy-1,2-propanediol with an ee-value of 86% have been prepared on a gram-scale using whole cells of A. niger M200. An enantiomeric ratio of approximately 100 has been determined under optimised biotransformation conditions with the partially purified epoxide hydrolase from A. niger M200. The regioselectivity of this enzyme was determined to be total for both (S)-tert-butyl glycidyl ether and (R)-tert-butyl glycidyl ether.
Keywords: biotransformace; Biotransformation; Aspergillus niger; fungální proteiny; Epoxy Compounds; epoxidové sloučeniny; financování organizované; Gram-Positive Bacteria; hydrolýza; Bacterial Proteins; substrátová specifita; Fungal Proteins; Epoxide Hydrolases; Financing, Organized; Substrate Specificity; grampozitivní bakterie; bakteriální proteiny; epoxid hydrolasy; Hydrolysis